Influence of Ralgro® on suckling calf performance on tall fescue pastures with various levels of endophyte infestation - Brazle, F.; Whittier, J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four hundred and ten cow-calf pairs were allotted to tall fescue pastures containing 40, 45, or 70% endophyte fungus infestation. One half of the calves in each pasture were implanted with Ralgro® initially and reimplanted about 110 days later. Calf gains on the 70% endophyte fungus pasture showed a greater (P<.05) response to implanting than those grazing the 40 and 45% endophyte-infested tall fescue pastures during the 165 day trial.
Keywords: Beef; Ralgo®; Performance; Fescue; Endophyte